2019
DOI: 10.1186/s12913-019-4095-0
|View full text |Cite
|
Sign up to set email alerts
|

An implementation science study to enhance cardiovascular disease prevention in Mukono and Buikwe districts in Uganda: a stepped-wedge design

Abstract: Background Uganda is experiencing a shift in major causes of death with cases of stroke, heart attack, and heart failure reportedly on the rise. In a study in Mukono and Buikwe in Uganda, more than one in four adults were reportedly hypertensive. Moreover, very few (36.5%) reported to have ever had a blood pressure measurement. The rising burden of CVD is compounded by a lack of integrated primary health care for early detection and treatment of people with increased risk. Many people have less ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 17 publications
(36 citation statements)
references
References 35 publications
0
36
0
Order By: Relevance
“…These factors could also offer an explanation for the high demand for biomedical interventions from CHWs. Cognizant of these gaps, the design of the overall project intervention incorporated a health facility intervention to build the capacity of health workers at the primary health care and higher levels to better prevent and manage NCDs [23]. The health worker training focuses on equipping them with better communication skills and improving the patient -provider and provider -CHW relationships.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These factors could also offer an explanation for the high demand for biomedical interventions from CHWs. Cognizant of these gaps, the design of the overall project intervention incorporated a health facility intervention to build the capacity of health workers at the primary health care and higher levels to better prevent and manage NCDs [23]. The health worker training focuses on equipping them with better communication skills and improving the patient -provider and provider -CHW relationships.…”
Section: Discussionmentioning
confidence: 99%
“…The community CVD programme includes working with CHWs, existing networks and community structures to promote knowledge, improved lifestyles, risk assessment and cardiovascular health as previously described [23]. The programme involves training of CHWs to conduct health education, promote lifestyle change through motivational interviewing and goal setting techniques, screen for risk factors at the community using non laboratory tools, and conduct house-to-house visits within their communities.…”
Section: Description Of Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…The data utilised for this risk factor mapping and analysis is drawn from the baseline survey conducted in December 2018 and January 2019 to benchmark key indicators for a type 2-hybrid stepped-wedge (SW) trial reported elsewhere [6]. The baseline was conducted in 20 parishes (Fig.…”
Section: Design and Setting Of The Studymentioning
confidence: 99%
“…The SPICES Project is a Horizon 2020 project financed by the European Commission that aims to address the CVD burden [22]. The overall objective is to implement and evaluate a comprehensive cardiovascular disease (CVD) prevention and care program at the community level in five countries (Belgium, France, South Africa, Uganda, and UK), to identify and compare barriers and facilitators for implementation across study contexts and to develop a learning community.…”
Section: Introductionmentioning
confidence: 99%